Hadith #2832 - Sunan Abi Dawud - Abdullah bin 'Uthman bin Khuthaym عبد الله بن عثمان بن خثيم القاري; Aisha bint Abi Bakr; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yusuf bin Mahk يوسف بن ماهك الفارسي (Sunan Abi Dawud)
Fara’ was the first animal born to them (the Arabs) which they sacrificed.
Grade: Sahih

Hadith #3877 - Sunan Abi Dawud - Abdullah bin 'Uthman bin Khuthaym عبد الله بن عثمان بن خثيم القاري; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
I brought my son to the Messenger of Allah (ﷺ) while I had compressed his uvula for its swelling. He said : Why do you afflict your children by squeezing for a swelling in the Uvula ? Apply this Indian aloes wood, for it contain seven types of remedies, among them being a remedy for pleurisy. It is applied through the nose for a swelling of the uvula poured into the side of the mouth for pleurisy. Abu Dawud said : By aloes wood he meant costus.
Grade: Sahih

Hadith #4060 - Sunan Abi Dawud - Abdullah bin 'Uthman bin Khuthaym عبد الله بن عثمان بن خثيم القاري; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
We asked Anas b. Malik: Which cloth was dearer to the Messenger of Allah (ﷺ) ? or Which cloth did the Messenger of Allah (ﷺ) like best to wear ? He replied: The striped cloaks (hibrah).
Grade: Sahih